The effects of EFL wordlist and proficiency on vocabulary knowledge - Bao, Zhen; Peng, Cheng (Frontiers in Psychology, 2024)
The Gaokao Word List (GWL) in China serves as a guideline for learning L2 vocabulary, but there are few studies verifying its effect on university EFL learners' vocabulary knowledge.Method: This study investigated the effects of the GWL and EFL proficiency on 66 Chinese university EFL learners' vocabulary knowledge by administering word recognition tests.The results showed that: 1) the GWL had significant effects on participants' receptive vocabulary knowledge; 2) EFL proficiency had significant effects on participants' word recognition, without interaction with the GWL. These findings were discussed through the lens of frequency of exposure, accounting for the overwhelming GWL effect on learners' vocabulary knowledge. We suggest EFL proficiency be taken into consideration when the GWL is revised in the future, to smoothen the transition in vocabulary learning from high school to university, and improve vocabulary learning efficiency.